2015
DOI: 10.1371/journal.pone.0117916
|View full text |Cite
|
Sign up to set email alerts
|

Solomonseal Polysaccharide and Sulfated Codonopsis pilosula Polysaccharide Synergistically Resist Newcastle Disease Virus

Abstract: Five combinations of three ratios (PS9-sPS1, PS7-sPS3 and PS6-sPS4) were prepared with polysaccharide (PS) and sulfated polysaccharide (sPS). The antiviral activities of these compounds were subsequently compared in vitro using the MTT assay, observation of the virus structure and immunofluorescence. The results demonstrated that SP9-sCP1, CP7-sCA3, EP7-sAP3, CA9-sEP1 and EP7-sCA3 presented higher activities, and SP9-sCP1 displayed the highest virus inhibition rate and clearly killed the virus and inhibited vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Hepatocellular carcinoma is a primary liver cancer to which most liver cancers belong. As a malignant tumor originating from the liver epithelial or mesenchymal tissue, it is prone to vascular invasion and metastasis, which mainly develop in the portal vein or its branches, hepatic veins or its branches, and the inferior vena cava of the liver, and homotype clumping in the portal vein is the most common form of metastasis of hepatocellular carcinoma [2][3][4][5][6][7][8][9][10][11][12]. The etiology and exact molecular mechanism are still unclear, and it is currently considered to be a multifactor and multistep complex process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hepatocellular carcinoma is a primary liver cancer to which most liver cancers belong. As a malignant tumor originating from the liver epithelial or mesenchymal tissue, it is prone to vascular invasion and metastasis, which mainly develop in the portal vein or its branches, hepatic veins or its branches, and the inferior vena cava of the liver, and homotype clumping in the portal vein is the most common form of metastasis of hepatocellular carcinoma [2][3][4][5][6][7][8][9][10][11][12]. The etiology and exact molecular mechanism are still unclear, and it is currently considered to be a multifactor and multistep complex process.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment types mainly include surgery, hepatic artery ligation, radiofrequency, freezing, laser, microwave, and chemotherapy. Many studies have shown that Codonopsis pilosula polysaccharides have a variety of biological functions, including cardiovascular and cerebrovascular protection, enhancing immunity and antitumor activities [4][5][6][7][8][9][10][11]. Based on all facts above, we studied human hepatoma HepG2 cells and further investigated the effect of Codonopsis pilosula polysaccharides on the proliferation and metastasis ability of hepatoma cells in vitro and its possible mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, GRb1/IL-4@CS/CaP-IBDV, CS/CaP-IBDV and GRb1 nanoparticles with different concentrations (0–500 μg/mL) were added, and cultured at 37 °C for 48 h. The MTT method was used to detect the cell activity of GRb1/IL-4@CS/CaP-IBDV, CS/CaP-IBDV and GRb1 against dendritic cells. The MTT detection method was used, as previously reported [ 25 ]. The OD value at 450 nm was measured by an enzyme-labeled instrument.…”
Section: Methodsmentioning
confidence: 99%
“…Liu et al (2015) prepared SP 9 -sCP 1 with polysaccharide (PS) and sulphated polysaccharide (sPS), which showed good viral killing and inhibition of viral antigen expression. This suggests that SP 9 -sCP 1 has high antiviral efficacy and could be used as a new antiviral drug [ 110 ]. Xing et al (2021) investigated the antiviral activity of Platycodon grandiflorus polysaccharides (PGPS) and virus-induced autophagy in the anti-PRV effect of PGPSt in PK-15 cells.…”
Section: Biological Activities Of Mfhpsmentioning
confidence: 99%